New approaches to the state of necessity in customary international law: insights from WTO law and foreign investment law (2021)
Both the International Court of Justice (“ICJ”) in the Case Concerning The Gabcikovo-Nagymaros Project (Hungary/Slovakia), and the International Law Commission (“ILC”) in its commentaries to its Articles on State Responsibility have pointed out that the requirements for the successful invocation of the defense of necessity embodied in Article 25 of the ILC's Articles on State Responsibility (“ILC's Articles”) need to be interpreted narrowly in order to prevent the abuse of this provision and the ensuing effect of justifying wrongful international acts. The result is that Article 25 is a provision the availability of which to States seems very limited, even in extreme circumstances. This article has shown that the recent case law in foreign investment law regarding the state of necessity under customary international law mainly follows the ICJ and the ILC and is, therefore, marked by a strict approach to the interpretation of Article 25 of the ILC's Articles. However, the article reveals that this approach is not the only one possible regarding Article 25, and that the WTO model of necessity could also be applied in the context of this provision.